AB0621 From Vedoss To Established Systemic Sclerosis Diagnosis According To The New ACR/EULAR 2013 Classification Criteria: A French-Italian Capillaroscopic Survey. (15th July 2016) - Vasile, M.; Avouac, J.; Sciarra, I.; Stefanantoni, K.; Iannace, N.; Allanore, Y.; Riccieri, V.
Abstract : Background: NailfoldCapillaroscopy (NC) is a diagnostic and sensitive tool in order to investigate Raynaud's phenomenon (RF) that is the hallmark of both Systemic Sclerosis (SSc) and Very Early Diagnosis Of ScS (VEDOSS) patients. Thus NC is largely used in patients with these conditions and NC specific abnormalities have become a minor criteria in ACR/EULAR SSc Criteria in 2013. Objectives: Aim of our study was to monitor NC changes in a group of 66 VEDOSS patients, enrolled in two EUSTAR center. Methods: We selected those patients who developed SSc at the follow-up. Moreover, we compared the NC features of these patients with NC of those VEDOSS patients who did not move to SSc, in order to find out NC features, if any, suitable as predictive risk factor for SSc at the time of VEDOSS diagnosis. Results: In our 66 VEDOSS patients, 21 of them (19 females, mean age 55 yrs) shifted to SSc in a mean follow-up time of 31 months (range 6–60 months). Table 1 shows the main features of matched VEDOSS patients: Group A with unchanging diagnosis and Group B progressing into SSc. Table 2 shows the progression of NC abnormalities from VEDOSS to established SSc diagnosis in Group B patients. When we compared basal NC of Group A and Group B patients, in former VEDOSS developing SScwe found a significantly higher NC score (>1), 13 versus 5 cases (p<0.03) and a larger mean apex width, 177 μm (range 50–640) versus 104 μm (range 10–280) (p<0.005). Conclusions: Our study describes a progression of NC changes during the evolution of early SSc. Moreover we identified some NC features, such as higher NC score and larger apex width, whose presence at the very early diagnosis of SSc may suggests its development in an established disease, thus underlying the relevance of specific NC abnormalities as possible predictive risk factors. Disclosure of Interest: None declared